Study on impact resistance behaviors of a novel composite laminate with basalt fiber for helical-sinusoidal bionic structure of dactyl club of mantis shrimp. (15th June 2020) - Han, Qigang; Shi, Shaoqian; Liu, Zhanhang; Han, Zhiwu; Niu, Shichao; Zhang, Junqiu; Qin, Hanlin; Sun, Yanbiao; Wang, Jiahui
Abstract: The microstructure of the dactyl club of mantis shrimp is mainly divided into two regions, the impact region and the periodic region, which their synergy make the dactyl club have better impact resistance. It is provided innovative inspiration by two regions cooperation for the manufacture of high-energy absorption and impact-resistant fiber composite laminates. In this paper, a novel dactyl-inspired helical-fiber sinusoidal-structure laminate (HSL) was manufactured by unidirectional basalt fiber prepreg based on the impact region and the periodic region of dactyl club. The experimental results confirmed the accuracy of the finite element simulation results. The HSL was compared with unidirectional-fiber flat laminate (UFL), unidirectional-fiber sinusoidal-structure laminate (USL) and helical-fiber flat laminate (HFL) in low-velocity impact tests. As a result, the maximum impact peak force of the HSL was 6593.45 N, which increased of 65.29%, 108.05% and 13.00% compared with that of the UFL (3988.80 N), USL (3169.21 N) and HFL (5835.20 N). Although the UFL and USL had higher absorption energy, they all have different degrees of damage, and under the same conditions, the HSL had less damage than HFL, indicating that the HSL had better impact resistance. The excellent performance of the HSL could be attributed to the helical-sinusoidal structure. The helical arrangement of the fibers enhances the resistance of the HSL, makes crackle propagation difficult. The sinusoidal structure of the HSL enhanced its cushioning ability for impact forces. Therefore, the HSL is suitable for parts that require better impact resistance.